Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) terhadap Efektivitas Belajar Siswa Kelas V - Purnomo, Riyan Aji; Fath, Ayatullah Muhammadin Al; Purnamasari, Mega Isvandiana (PGSD STKIP PGRI Pacitan, 2021)
The purpose of this study is to (1 ) Usage Model Cooperative Learning Teams Games Tournament (TGT) On the Effectiveness of Student Class V Elementary School (2) Knowing the results of Model Cooperative Learning Teams Games Tournament (TGT) Student Class V Elementary School (3) Knowing the benefits of Model Cooperative Learning Teams Games Tournament ( TGT) Grade V Elementary School Students. This study uses qualitative research where this study uses analytical techniques The results showed that (1) the use of the TGT learning method increased student learning activities. (2) The results of the maximum ability shown by students on each indicator, namely on the indicator of student attention there are 5 students who achieve good abilities. (3) The benefits of the cooperative learning model are Teams Games Tournament (TGT) very well received by students, students work together with their groups, respect the opinions of other groups, are able to present their opinions well, and this learning model is also used as an alternative in the learning process.